Young Adolescents’ Leisure Patterns - Zeijl, Elke; Bois-Reymond, Manuela; Poel, Yolanda (Loisir et Société / Society and Leisure)

(untitled) (Presses de l’Université du Québec, 2001)
AbstractUntil recently, studies into juveniles’ leisure activities concentrated mainly on adolescents. In this study, the leisure activities of both pre-adolescents and adolescents are studied. Departing from sociological debates on the busyness of contemporary young adolescents’ leisure diaries and of an advanced onset of the transition from childhood into the youth phase, a questionnaire was designed for 10 to 15 year-olds. 927 Dutch youngsters were studied. By means of CATPCA, it was found that 10-12 year-old girls mainly engage in reading and in creative activities, whereas the boys spend most time playing outside. Fourteen and fifteen year-olds, on the other hand, showed a clear interest in youth-cultural activities, which did not support theoretical notions about the advancement of adolescence at the expense of childhood. Questions on organized activities showed that the market of leisure opportunities is not equally accessible to everyone: higher class kids are in an advantageous position compared to lower class kids, which affects the degree to which these subgroups have the opportunity to develop important leisure capital through informal learning.